Selective collection as environmental preservation instrument and income source - Souza, Everaldo Oliveira de; Frias, Danila Fernanda Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The accumulation of solid waste causes environmental deterioration and implications for quality of life, so selective collection emerges as an alternative to reduce this impact. The objective of this study was to evaluate the socioeconomic, demographic and work profiles of waste pickers in Ilha Solteira, São Paulo and to analyze the importance of this practice for subsistence and environmental preservation. For this, 22 waste pickers were interviewed and information was collected from the City Hall. Among the respondents, 72.7% were male, 54.5% married, 54.6% lived favorably, 40.9% reported being in the activity for more than 5 years, 90.9% are due to unemployment and 66, 3% stated that they consider the practice of grooming very important for maintaining the city cleaner. Regarding the data obtained from the City Hall, it was found that, on its website, disclosure of a series of information on how citizens can help in the selective collection and control of waste generated. The profession of scavenger proved to be very important because many people use this practice as an occupation and source of income to support their families. The collection must be performed in a dignified manner and have due appreciation and recognition by society.